Cuba : la revolución y sus raíces históricas - Thomas, Hugh (Estudios Internacionales, 1971)
This article examines some of the main characteristics of modern Cuba, in order to determine which were the significant factors of the process that culminated with the revolution and may have influenced it. The first characteristic to consider is posed in the form of a racial question: What is a Cuban? The second lies in the fact that the island was a Spanish colony for longer than any other. It should also be considered that Cuba was for almost 30 years after its nominal independence virtually a political colony of the United States. And finally, it is necessary to mention two other factors: first, the special role of sugar in the development of the Cuban economy and the special characteristics of its society, so different from those of the rest of Latin America.